Calculations of spectral output of a novel graphene light source integrated with electrostatically actuated membrane - Kozłowska, Anna; Lesniewska-Matys, Kamila (Photonics Letters of Poland, 2025)
Calculations of spectral output of a graphene light source integrated with electrostatically actuated membrane were performed, taking into account the light source geometry and the deflection range of silicon membrane. Concept of miniaturized, tuneable light source operating in IR spectral range is presented. Maximum wavelength tuneability is discussed. Full Text: PDF References M. Junaid, M.H. Md Khir, G. Witjaksono, Z. Ullah, N. Tansu, M.S. Saheed, P. Kumar, L. Hing Wah, S.A. Magsi, M.A. Siddiqui, "A Review on Graphene-Based Light Emitting Functional Devices", Molecules 25(18), 3646 (2020). CrossRef Y.D. Kim, H. Kim, Y. Cho, J.H. Ryoo, C.H. Park, P. Kim, Y.S. Kim, S. Lee, Li, S.N. Park, Y. Shim Yoo, D. Yoon, V.E. Dorgan, E. Pop, T.F. Heinz, J. Hone, S.H. Chun, H. Cheong, S.W. Lee, et al., "Bright visible light emission from graphene", Nat. Nanotechnol. 10(8), 676 (2015). CrossRef Y.D. Kim, Y. Gao, R.J. Shiue, L. Wang, O.B. Aslan, M.H. Bae, H. Kim, D. Seo, H.J. Choi, S.H. Kim, A. Nemilentsau, T. Low, C. Tan, D.K. Efetov, T. Taniguchi, K. Watanabe, K.L. Shepard, T.F. Heinz, D. Englund, et al., "Ultrafast Graphene Light Emitters", Nano Lett. 18, 934 (2018). CrossRef L. Ghirardini, E.A.A. Pogna, G. Soavi, A. Tomadin, P. Biagioni, S. Dal Conte, S. Mignuzzi, D. De Fazio, T. Taniguchi, K. Watanabe, L. Duò, M. Finazzi, M. Polini, A.C Ferrari, G. Cerullo, M. Celebrano, "Tunable broadband light emission from graphene", 2D Mater. 8, 035026 (2021). CrossRef P. Gowda, D.A. Patient, S.A.R. Horsley, G.R. Nash, "Erratum: “Toward efficient and tailorable mid-infrared emitters utilizing multilayer graphene” [Appl. Phys. Lett. 120, 051105 (2022)]", Appl. Phys. Lett. 120, 051105 (2022). CrossRef N. Negm, S. Zayouna, S. Parhizkar, P.S. Lin, P.H. Huang, S. Suckow, S. Schroeder, E. DeLuca, F.O. Briano, A. Quellmalz, G. Duesberg, F. Niklaus, K.B. Gylfason, M.C. Lemme, "Graphene Thermal Infrared Emitters Integrated into Silicon Photonic Waveguides", ACS Photonics, 11, 2961 (2024). CrossRef Research, "Development and characterization of a TunAble Graphene liGht Emitting hybrid MOEMS Device - TAGGED", DirectLink S. Nazir, O.S. Kwon, "Micro-Electromechanical Systems-based Sensors and Their Applications", Appl. Sci. Converg. Technol. 31(2), 40 (2022). CrossRef X. Han, M. Huang, Z. Wu, Y. Gao, Y. Xia, P. Yang, S. Fan, X. Lu, X. Yang, L. Liang, W. Su, L. Wang, Z. Cui, Y. Zhao, Z. Li, L. Zhao, Z. Jiang, "Advances in high-performance MEMS pressure sensors: design, fabrication, and packaging", Microsystems Nanoeng. 9(1), 156 (2023). CrossRef I. Kanno, J. Ouyang, J. Akedo, T. Yoshimura, B. Malič, P. Muralt, "Piezoelectric thin films for MEMS", Appl. Phys. Lett. 122(9), 90401 (2023). CrossRef V.E. Dorgan, A. Behnam, H.J. Conley, K.I. Bolotin, E. Pop, "High-Field Electrical and Thermal Transport in Suspended Graphene", Nano Lett. 13, 4581 (2013). CrossRef R. Jóźwicki, Instrumental Optics, (Warszawa, Wydawnictwa Naukowo-Techniczne, in Polish, 1970). DirectLink Filmetrics® Spectral Reflectance Calculator DirectLink